Iodine-Driven Three-Component Reaction of Isocyanides, Amines, and TsNXNa (X = Br, Cl): A Facile, Metal-Free Approach towards N-Sulfonyl Guanidines - Kashyap, Sauvik; Phukan, Prodeep (Synlett, 2025)
This work illustrates an expeditious, highly efficient, metal-, base-, and oxidant-free approach towards synthesizing N-sulfonyl guanidines via a three-component reaction system comprising isocyanides, amines, and TsNXNa (X = Br, Cl). The reaction proceeds via the formation of an isolable carbodiimide intermediate. The synthetic protocol emerges as a promising route for a simple, efficient, and rapid transformation into a diverse range of N-sulfonyl guanidines under mild reaction conditions.
Keywords: isocyanide; bromamine-T; carbodiimide; metal-free; guanidine